2007
DOI: 10.1016/j.tetlet.2007.07.129
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of tetrazole analogues of amino acids using Fmoc chemistry: isolation of amino free tetrazoles and their incorporation into peptides

Abstract: Abstract-An efficient synthesis of tetrazole analogues of amino acids starting from N a -Fmoc amino acid in a three-step protocol is reported. The free amino tetrazoles were obtained in good yields and with excellent purity after removal of the Fmoc group. The synthesis of analogues of aspartic and glutamic acids in which the 5-tetrazolyl moiety is inserted at the b/c carboxyl group starting from Fmoc-Asn and Fmoc-Gln and the incorporation of these tetrazoles into peptides are also described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 24 publications
1
28
0
Order By: Relevance
“…Initial synthesis of tetrazole 12 was carried out using NaN 3 and ZnBr 2 in a mixture of H 2 O-i-PrOH conditions reported by Sharpless et al 8 The synthesis of the tetrazole-containing glutamic acid using these conditions was unsuccessful in our hands despite the synthesis of an analogous Fmoc-protected tetrazole-containing glutamic acid having been reported previously. 9 It was suspected in our case that hydrolysis of the ester group by water was occurring under these conditions. This was confirmed by the observation of benzyl alcohol in the 1 H NMR spectrum of the crude product.…”
Section: Scheme 1 Synthesis Of Tetrazole-containing Analogues 2 Andmentioning
confidence: 68%
See 1 more Smart Citation
“…Initial synthesis of tetrazole 12 was carried out using NaN 3 and ZnBr 2 in a mixture of H 2 O-i-PrOH conditions reported by Sharpless et al 8 The synthesis of the tetrazole-containing glutamic acid using these conditions was unsuccessful in our hands despite the synthesis of an analogous Fmoc-protected tetrazole-containing glutamic acid having been reported previously. 9 It was suspected in our case that hydrolysis of the ester group by water was occurring under these conditions. This was confirmed by the observation of benzyl alcohol in the 1 H NMR spectrum of the crude product.…”
Section: Scheme 1 Synthesis Of Tetrazole-containing Analogues 2 Andmentioning
confidence: 68%
“…Sureshbabu et al 9 reported that deprotection of Boc-Phe tetrazole using TFA was unsuccessful. In the present work, deprotection of the Boc group using TFA led to formation of tert-butylated byproducts despite the use of scavengers (H 2 O-triisopropylsilane).…”
Section: Scheme 1 Synthesis Of Tetrazole-containing Analogues 2 Andmentioning
confidence: 99%
“…Our group reported several new classes of peptidomimetics possessing heterocycles such as 1,3,4,-oxadiazole, 15 1,2,4,-oxadiazole, 16 1,3,4,-thiadiazole, 17 triazoles 18 and tetrazoles. 19 This list also includes Fmoc-protected amino alkyl S/Se-linked tetrazoles 20 and Z/Boc-protected S-linked oxadiazole tethered peptidomimetics. 21 Thus, with the continuing interest in designing heterocycle tethered peptidomimetics we envisaged the synthesis of the S-linked 1,3,5-triazine moiety incorporated into the peptide backbone.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…12 On the other hand, compounds containing the thiazole nucleus have also been reported to exhibit various biological activities, the specificity of action often being dictated by the attached functionalities. 13 Thiazole-containing heterocyclic peptides, such as nosiheptide, GE2270 A and nocathiacin, [14][15][16][17] isolated from marine organisms, exhibit potent biological profiles ─ observations which support the inclusion of the thiazole nucleus in the design of lead compounds in the development of new active pharmaceutical ingredients (APIs). 18 Attention has thus been given to the development of novel compounds which contain both the styryl and thiazole moieties and, in this communication, we report the preparation and biological screening of a series of styrylthiazoles 4, (E)-2-[(naphthalen-1-yl)vinyl]thiazoles and their cinnamic acid precursors.…”
Section: Introductionmentioning
confidence: 99%